Molecular and epidemiological evidence of patient-to-patient hepatitis C virus transmission in a Scottish emergency department. Issue 4 (April 2018) - Johannessen, I.; Danial, J.; Smith, D.B.; Richards, J.; Imrie, L.; Rankin, A.; Willocks, L.J.; Evans, C.; Leen, C.; Gibson, P.; Simmonds, P.; Goldberg, D.; et al.
Summary: Background: Transmission of hepatitis C virus (HCV) in the healthcare setting is rare. Routine infection prevention and control measures mean that this should be a preventable 'never event'. Aim: To investigate the diagnosis of acute healthcare-associated HCV infection. Methods: Epidemiological and molecular investigation of a case of acute HCV infection associated with nosocomial exposure. Findings: Detailed investigation of the treatment history of a patient with acute HCV infection identified transmission from a co-attending patient in an emergency department as the likely source; this possibility was confirmed by virus sequence analysis. The precise route of transmission was not identified, though both patient and source had minimally invasive healthcare interventions. Review of infection, prevention and control identified potentially contributory factors in the causal pathway including hand hygiene, inappropriate use of personal protective equipment, and blood contamination of the surface of the departmental blood gas analyser. Conclusion: We provide molecular and epidemiological evidence of HCV transmission between patients in an emergency department that was made possible by environmental contamination. Patients with HCV infection are higher users of emergency care than the general population and a significant proportion of those affected remain unknown and/or infectious. Equipment, departmental design, staff behaviour, and patient risk require regular review to minimize the risk of nosocomial HCV transmission.